Screening for cervical cancer among women in five countries in sub-saharan Africa: analysis of the role played by distance to health facility and socio-demographic factors - Kwamena S. Dickson; Ebenezer N. K. Boateng; Evelyn Acquah; Castro Ayebeng; Isaac Y. Addo (BMC, 2023)
Abstract Background Cervical cancer significantly affects women in Sub-Saharan Africa (SSA). However, limited studies have concentrated on cervical screening behaviour among women in SSA. This study aimed to assess the interplay of distance to health facilities and socio-demographic factors with cervical screening behaviour among women in five SSA countries. Methods The study was based on pooled data of 40,555 women included in Demographic and Health Surveys (DHS) conducted between 2013 to 2021. Proportions and logistic regression models were used in assessing the interplay of distance to health facilities and socio-demographic factors with cervical screening behaviour. Results Approximately, 7.9% of women that saw the distance to a health facility as a big problem, tested for cervical cancer compared to 13.5% who indicated that distance to a health facility is not a big problem. More women in urban areas, with a higher level of education, of richest wealth index, aged 40-44 years and using contraceptives who also indicated that distance to a health facility was a big problem tested for cervical cancer compared to those in rural areas with no education, of poorest wealth index, aged 15-19 years and not using contraceptives. Education, age, contraceptive use, frequent exposure to mass media and Sexual Transmitted Infections (STI) had a significant relationship with testing for cervical cancer. Conclusion The prevalence of cervical cancer screening was low in the five SSA countries largely due to distance barriers and was also significantly influenced by education, age, contraceptive use, frequent exposure to mass media, and STI status. To improve the screening for cervical cancer and its associated benefits in the five SSA countries, there is a need for policymakers, clinicians and public health workers to channel more commitment and efforts to addressing the barriers identified in this study.